THE ROLE OF MANAGEMENT INFORMATION SYSTEMS IN THE TRANSPORTATION INDUSTRY (PT. KERETA API INDONESIA) - Faeni, Dewi Puspaningtyas; Fadilah , Nayla Nur (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
Indonesian Railways (Persero) or PT. KAI is a passenger transportation service provider that requires a ticket to access the train. To make ticket ordering easier, PT. KAI has launched KAI Access, the official online train ticket booking application. This application makes it easier for people to order tickets without having to queue at stations or convenience stores. However, there are still many ordinary people who are confused or don't understand how to order tickets online via the KAI Access application. To overcome this problem, an attractive and easy-to-understand approach to introducing the KAI Access application is needed, as well as an effective advertising environment. Motion graphics are considered the right solution, because they are an effective and attractive means of communication and advertising by combining images, color, sound and movement. Motion graphics can be used to create dynamic and effective communication designs, so that they can attract public interest in using the KAI Access application.